2014
DOI: 10.15666/aeer/1201_105122
|View full text |Cite
|
Sign up to set email alerts
|

Metals in Sediment and Phragmites Australis (Common Reed) From Tisza River, Serbia

Abstract: Abstract. In this study the concentrations of metals were investigated in Phragmites australis (Cav.) Trin. eh Steud. 1841 and sediment samples from the bed of the River Tisza in Serbia. Al, As, B, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, Sr and Zn levels were analyzed using inductively coupled plasma -optical emission spectrometry. The sediment samples contained elevated concentrations of cadmium, chromium, copper, nickel and zinc. The increased concentration of these metals had no significant effect on wildli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
(39 reference statements)
0
11
1
Order By: Relevance
“…The studies of [15] [22] in the estuaries of Italian rivers affected by municipal wastewaters and agricultural activities showed a good correlation of Al, As, Cr, Cu, Mn, Ni and Zn in P. australis with the elemental content in corresponding sediments and water. Also a strong positive correlation between the concentrations of Al, As, Co, Cr, Cu, Fe, Mn, Ni, Se, Sr and Zn in the sediments and all organs (rhizome, stem and leave) of P. australis sampled from the Tisza River in Serbia was found by [23]. The investigations in the constructed wetland in North Italy [24] and in the Hokersar wetland, Ramsar site of Kashmir Himalaya, India [25] showed that P. australis is appropriate species for phytoextraction and phytoremediation of the environment.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The studies of [15] [22] in the estuaries of Italian rivers affected by municipal wastewaters and agricultural activities showed a good correlation of Al, As, Cr, Cu, Mn, Ni and Zn in P. australis with the elemental content in corresponding sediments and water. Also a strong positive correlation between the concentrations of Al, As, Co, Cr, Cu, Fe, Mn, Ni, Se, Sr and Zn in the sediments and all organs (rhizome, stem and leave) of P. australis sampled from the Tisza River in Serbia was found by [23]. The investigations in the constructed wetland in North Italy [24] and in the Hokersar wetland, Ramsar site of Kashmir Himalaya, India [25] showed that P. australis is appropriate species for phytoextraction and phytoremediation of the environment.…”
Section: Introductionmentioning
confidence: 88%
“…were used. P. australis is one of the most distributed macrophytes in aquatic ecosystems, and numerous studies showed its capacity of trace element bioaccumulation [11] [13] [15] [19] [20] [21] [23]. Thus Duman [19] reported that the roots of Phragmites australis from fresh water Lake Sapanca in Turkey were found to be good accumulators of Cu, Mn, Ni, Zn.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of in the estuaries of Italian rivers affected by municipal wastewaters and agricultural activities showed a good correlation of Al, As, Cr, Cu, Mn, Ni and Zn in P. australis with the elemental content in corresponding sediments and water. Also a strong positive correlation between the concentrations of Al, As, Co, Cr, Cu, Fe, Mn, Ni, Se, Sr and Zn in the sediments and all organs (rhizome, stem and leave) of P. australis sampled from the Tisza River in Serbia was found by [23]. The investigations in the constructed wetland in North Italy [24] and in the Hokersar wetland, Ramsar site of Kashmir Himalaya, India [25] showed that P. australis is appropriate species for phytoextraction and phytoremediation of the environment.…”
Section: Introductionmentioning
confidence: 88%
“…To extend our studies regarding the elemental content of more than 35 elements for the territory of an important but poor investigated recreation zone of the Caucasian coast of the Black Sea, the aquatic macrophytes Phragmites australis, Carex conescens L as well as the green algae Cladophora sericea (Hudson) Kutzing were used. P australis is one of the most distributed macrophytes in aquatic ecosystems, and numerous studies showed its capacity of trace element bioaccumulation [19][20][21][22][23]. Thus Duman reported that the roots of Phragmites australis from fresh water Lake Sapanca in Turkey were found to be good accumulators of Cu, Mn, Ni, Zn.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with the findings of other studies demonstrating that accumulated metals in the common reed are not distributed evenly. The underground organ shows a higher storage capacity than the above ground parts (Štrbac et al, 2014;Kucaj et al, 2015). Nouri et al, (2009) reported that the root tissues accumulate higher concentrations of metals than shoots, which indicated greater plant availability of the substrate metals, as well as interior limited mobility of the plant.…”
Section: Heavy Metals In Plantmentioning
confidence: 99%